Menstrual Cycle Length and Dysmenorrhea in Female Adolescents Aged 9-18 Years - Monica, Agnes; Lilis; Kurniawan, Felicia; Padang, Astrid Fransisca (Indonesian Journal of Obstetrics and Gynecology, 2023)
Abstract Objective: To determine the relationship between menstrual cycle length and dysmenorrhea in female adolescents aged 9-18 years in Sang Timur Tomang School West Jakarta. Methods: This study used a cross-sectional study approach to conduct observational analytic research. The study samples were female students aged 9-18 years in Sang Timur Tomang School. Study data were obtained through the Verbal Multidimensional Scoring System (VMSS) questionnaire in Indonesian. The Chi-square test of independence was used to determine the relationship between menstrual cycle length and dysmenorrhea. Results: From a total of 137 respondents, 38% have abnormal menstrual cycle length. Eighty-two-point-seven percent of respondents who have abnormal menstrual cycle length experienced dysmenorrhea, and 17,3% of participants who have abnormal menstrual cycle length did not experience dysmenorrhea. Chi-square test results showed a significant relationship between menstrual cycle length and dysmenorrhea in female adolescents aged 9-18 years in Sang Timur Tomang School West Jakarta (p = 0,005). Conclusion: There is a significant relationship between menstrual cycle length and dysmenorrhea in female adolescents aged 9-18 years in Sang Timur Tomang School West Jakarta. Keywords: female adolescents, dysmenorrhea, menstrual cycle, menstrual cycle length